Comparison of Nasolabial Symmetry in Children with Repaired Unilateral Complete Cleft Lip and Non-Cleft Controls in Kano, Nigeria - Bardi, Martins; Adetokunbo, Adebola; Adeyemi, Efunkoya; Uchenna, Omeje; Ibiyinka, Amole; Rasheed, Suleiman; Anas, Bawa (Nigerian Journal of Basic and Clinical Sciences, 2025)
BackgroundAssessment of surgical outcomes following unilateral cleft lip repair may be incomplete without comparison with matched non-cleft controls from the same ethno-racial group, as nasal morphology varies across populations. Evaluating nasolabial symmetry in this context provides a more accurate understanding of reconstructive success.AimTo compare the nasolabial symmetry of children with repaired unilateral complete cleft lip—with or without palate involvement—with matched non-cleft controls in Kano, Nigeria.MethodsThis prospective comparative study assessed nasolabial symmetry in children who had undergone repair of a unilateral complete cleft lip and matched non-cleft children. Nasal parameters measured included nostril width, nostril height, and alar base width. Labial parameters included vertical lip height, vertical philtral height, horizontal lip length, and vermilion height. Data were analyzed using the independent sample t-test.ResultsComparison between cleft and non-cleft participants showed that only vermilion height demonstrated no statistically significant difference between the groups (p = 0.184, p = 0.790). All other nasal and labial parameters differed significantly, indicating persistent asymmetry despite surgical repair.ConclusionFollowing surgical repair of unilateral complete cleft lip in Kano, notable differences remain in several nasolabial parameters when compared with non-cleft peers. Cleft surgeons are encouraged to consider ethnic and regional norms of facial morphology during surgical planning to optimize aesthetic outcomes.
Keywords: Anthropometry; Nasolabial Symmetry; Unilateral Complete Cleft Lip and Palate